Hepatoprotective Effect of Citrus Sinensis Peel Extract Against Isoniazid and Rifampicin-induced Liver Injury in Wistar Rats - Edward Kosasih; Linda Chiuman; I Nyoman Ehrich Lister; Edy Fachrial (Faculty of Pharmacy, Universitas Gadjah Mada, 2019)
Tuberculosis (TB) is one of the leading causes of death in developing countries. One of the problems in controlling TB disease is that most anti-tuberculosis drugs are hepatotoxic. Citrus sinensis peel extract is the rich source of secondary metabolites with high potential effectiveness as an antioxidant. In the present study, we evaluate the hepatoprotective effect of Citrus sinensis peel ethanolic extract (CSPEE) on isoniazid and rifampicin-induced liver injury in Wistar rats. Twenty five adult male Wistar rats were divided into 5 groups of 5 each : control, (INH+RIF) (50 mg/kg bw once a day for 14 days), (INH+RIF) + various dose of CSPEE (300, 450, 600 mg/kg bw). CSPEE was given orally once a day for 14 days followed by administration of INH + RIF suspension. The measurement of serum ALT and AST were carried out on the 15th day. Histopathologic examination of the liver was also performed. The Serum ALT and AST of the rats that induced with INH + RIF were increased significantly (P<0.001) compare to those of control groups, and the histopathologic slides showed steatosis, vacuolation and necrosis of hepatic cells. The serum ALT and AST in groups treated with CSPEE were not significantly different (p>0.05) with those of control groups. The serum ALT and AST and histopathological examination of the liver of the group that administered 600 mg/kg CSPEE were closest to normal rats. Citrus sinensis peel extract exhibits hepatoprotective effect on liver injury induced with INH + RIF in Wistar rats.